A Simple Square Rooting Circuit Based on Operational Amplifiers (OPAMPs) - Selvam, K. C.; Latha, S. (Engineering, Technology & Applied Science Research, 2013)
A simple circuit which accepts a negative voltage as input and provides an output voltage equal to the square root of the input voltage is described in this paper. The square rooting operation is dependent only on the ratio of two resistors and a DC voltage. Hence, the required accuracy can be obtained by employing precision resistors and a stable reference voltage. The feasibility of the circuit is examined by testing the results on a proto type.